2015
DOI: 10.1080/09297049.2015.1014900
|View full text |Cite
|
Sign up to set email alerts
|

Developmental neuropsychological assessment of 4- to 5-year-old children born following Preimplantation Genetic Diagnosis (PGD): A pilot study

Abstract: The purpose of this pilot study was to evaluate developmental neuropsychological profiles of 4- to 5-year-old children born after Preimplantation Genetic Diagnosis (PGD). Twenty-seven participants received a neurological examination and a battery of neuropsychological assessments including Wechsler Preschool & Primary Scale of Intelligence - Third Edition (WPPSI-III; cognitive development), Preschool Language Scale, Fourth Edition (PLS-4; language development), Wide Range Assessment of Visual Motor Abilities (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…To date, only a few systematic studies have assessed the cognitive and socio-emotional development of children born after PGD. Internationally, data from five PGD cohorts have been published (Banerjee et al, 2008;Nekkebroeck et al, 2008aNekkebroeck et al, , 2008bNekkebroeck et al, , 2011Thomaidis et al, 2012;Sacks et al, 2015;Winter et al, 2014Winter et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few systematic studies have assessed the cognitive and socio-emotional development of children born after PGD. Internationally, data from five PGD cohorts have been published (Banerjee et al, 2008;Nekkebroeck et al, 2008aNekkebroeck et al, , 2008bNekkebroeck et al, , 2011Thomaidis et al, 2012;Sacks et al, 2015;Winter et al, 2014Winter et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, concerns persist about long-term neurocognitive outcomes for children conceived after PGD. Children born after PGD were evaluated at five years of age and showed normal developmental neuropsychological outcomes [43]. In contrast, preimplantation genetic screening (PGS) was found to be associated with inferior neurodevelopment in twins, but no specific difference was noted in singletons [44].…”
Section: Resultsmentioning
confidence: 99%
“…The follow-up of PGT children at a young age has been studied in smaller cohorts. Developmental neurological and cognitive assessment and follow-up on psychomotor and social functioning showed that PGT pre-schoolers were comparable with controls born after ICSI or after spontaneous conception [67][68][69][70]. Another study on body composition and blood pressure showed no adverse outcomes for 6-year-old children born after PGT (with day 3 embryo biopsy followed by blastocyst transfer) compared to children born after ICSI without embryo biopsy [71].…”
Section: Children Follow-upmentioning
confidence: 98%